European guideline for the management of scabies. (22nd June 2017) - Salavastru, C.M.; Chosidow, O.; Boffa, M.J.; Janier, M.; Tiplica, G.S.
Abstract: Scabies is caused by Sarcoptes scabiei var. hominis . The disease can be sexually transmitted. Patients' main complaint is nocturnal itch. Disseminated, excoriated, erythematous papules are usually seen on the anterior trunk and limbs. Crusted scabies occurs in immunocompromised hosts and may be associated with reduced or absent pruritus. Recommended treatments are permethrin 5% cream, oral ivermectin and benzyl benzoate 25% lotion. Alternative treatments are malathion 0.5% aqueous lotion, ivermectin 1% lotion and sulphur 6–33% cream, ointment or lotion. Crusted scabies therapy requires a topical scabicide and oral ivermectin. Mass treatment of large populations with endemic disease can be performed with a single dose of ivermectin (200 micrograms/kg of bodyweight). Partner management needs a look‐back period of 2 months. Screening for other STI is recommended. Patients and close contacts should avoid sexual contact until completion of treatment and should strictly observe personal hygiene rules when living in crowded spaces. Written information should be provided to suspected cases.